Model Project Based Learning Berbantuan Media Powerpoint Pada Kurikulum Merdeka Di Sekolah Dasar - Wibowo, Yusuf Rendi; Salfadilah, Fatonah (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2024)
The Project Based Learning (PJBL) learning model is an effective approach to overcome student boredom in the independent curriculum. This article aims to show that PJBL supported by PowerPoint (PPT) media is appropriate to be applied in learning. This study uses a qualitative method with a descriptive approach, as well as triangulation data analysis techniques. Data was collected through observation, interviews, and documentation at SDN 8 Tulang Bawang Barat Udik, with resource persons from grade IV educators. The results of the study show that the PJBL model assisted by PPT can improve the learning process. Important aspects of PJBL include: practical activities, problem-solving based on daily situations, placement of students as learning centers, and collaboration between students. PPT media functions to assist educators in conveying material and project steps. The advantage of this model is that it increases student engagement and creativity, as well as facilitates understanding of the material. However, there are weaknesses such as the need for long preparation and adequate infrastructure. Overall, PJBL assisted by PPT has proven to be effective in creating an active and fun learning atmosphere for students.